2022
DOI: 10.3390/jcm11030583
|View full text |Cite
|
Sign up to set email alerts
|

Content Validity and Reliability of the Pressure Ulcer Knowledge Test and the Knowledge Level of Portuguese Nurses at Long-Term Care Units: A Cross-Sectional Survey

Abstract: (1) Background: Improvement in pressure ulcer care depends both on the dissemination of knowledge and its implementation. This study aims to translate the Pressure Ulcer Knowledge Test into Portuguese from Portugal and evaluate the internal consistency of the questionnaire. The second aim is to assess nurses’ pressure ulcer knowledge level. (2) Methods: The Pressure Ulcer Knowledge Test was translated into Portuguese, and the translated test’s internal consistency and content validity were assessed. Further, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…However, the findings of 30% of the respondents from this study, who demonstrated only satisfactory knowledge is of concern, because they would put patients at risk. A concern for risk to patients owing to a lack of knowledge of pressure ulcers concurs with the reports by Dalvand et al (2018) and Furtado et al (2022) who indicated that ulcer development is associated with a lack of knowledge and incompetence in managing pressure ulcers among nurses.…”
Section: Student Nurses' Knowledge Of Pressure Ulcerssupporting
confidence: 68%
See 3 more Smart Citations
“…However, the findings of 30% of the respondents from this study, who demonstrated only satisfactory knowledge is of concern, because they would put patients at risk. A concern for risk to patients owing to a lack of knowledge of pressure ulcers concurs with the reports by Dalvand et al (2018) and Furtado et al (2022) who indicated that ulcer development is associated with a lack of knowledge and incompetence in managing pressure ulcers among nurses.…”
Section: Student Nurses' Knowledge Of Pressure Ulcerssupporting
confidence: 68%
“…Most developed (high-income) countries hire competent nurses to facilitate quality patient care and secure their market (Bahrambeygi et al 2019;Ortega et al 2020). In lower-income countries, the prevalence of a lack of knowledge on ulcer is noted as evidenced by incompetence among nurses especially in managing pressure ulcers (Dalvand et al 2018;Furtado et al 2022).…”
Section: Nurses' Knowledge Of Pressure Ulcersmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings showed inadequate knowledge among nurses regarding PU prevention. Furtado et al (2022) also reported that nurses scored lower on questions related to prevention and risk, with only two of the 221 nurses achieving 90% correct answers or more. Meanwhile, Tulek et al (2016) noted a lack of knowledge among nurses regarding PU prevention.…”
Section: Discussionmentioning
confidence: 99%